Предмет: Алгебра, автор: hdhudbe

решите пожалуйста прошу срочно

Приложения:

Ответы

Автор ответа: OPetroW
1

а)  (\frac{a-b}{a^{2} + ab} -\frac{a}{ab+b^{2}}) : (\frac{1}{a+b} - \frac{b^{2}}{ab^{2}-a^{3}}) =   (\frac{a-b}{a^{2} + ab} -\frac{a}{ab+b^{2}}) : (\frac{1}{a+b} - \frac{b^{2}}{ab^{2}-a^{3}}) =  </p><p>\\(\frac{a-b}{a(a+b)} -\frac{a}{b(a+b)}) : (\frac{1}{a+b} - \frac{b^{2}}{a(b^{2}-a^{2})}) =  
</p><p>\\(\frac{b(a-b)}{ab(a+b)} -\frac{a^{2}}{ab(a+b)}) : (\frac{1}{a+b} - \frac{b^{2}}{a(b-a)(b+a)}) =  
</p><p>\\ \frac{ba-b^{2}-a^{2}}{ab(a+b)} : (\frac{a(b-a)}{a(b-a)(b+a)} - \frac{b^{2}}{a(b-a)(b+a)}) =  
</p><p>\\ \frac{-a^{2}+ba-b^{2}}{ab(a+b)} : \frac{a(b-a)-b^{2}}{a(b-a)(b+a)} =  

 \frac{-a^{2}+ba-b^{2}}{ab(a+b)} : \frac{ab-a^{2}-b^{2}}{a(b-a)(b+a)} =  </p><p>\\ \frac{-a^{2}+ba-b^{2}}{ab(a+b)} : \frac{-a^{2}+ab-b^{2}}{a(b-a)(b+a)} =  </p><p>\\ \frac{-a^{2}+ba-b^{2}}{ab(a+b)} * \frac{a(b-a)(b+a)}{-a^{2}+ab-b^{2}} = \frac{b-a}{b}

2) (\frac{2ab}{a^{2}-b^{2}} + \frac{a-b}{2(a+b)})*\frac{2a}{a+b}-\frac{b}{a-b} =  \\ (\frac{2ab}{(a-b)(a+b)} + \frac{a-b}{2(a+b)})*\frac{2a}{a+b}-\frac{b}{a-b} =  \\ (\frac{4ab}{2(a-b)(a+b)} + \frac{(a-b)^{2}}{2(a+b)(a-b)})*\frac{2a}{a+b}-\frac{b}{a-b} =  \\ \frac{4ab+(a-b)^{2}}{2(a-b)(a+b)}*\frac{2a}{a+b}-\frac{b}{a-b} =  \\ \frac{4ab+a^{2}-2ab+b^{2}}{2(a-b)(a+b)}*\frac{2a}{a+b}-\frac{b}{a-b} =  \\ \frac{a^{2}+2ab+b^{2}}{2(a-b)(a+b)}*\frac{2a}{a+b}-\frac{b}{a-b} =  

 \frac{a^{2}+2ab+b^{2}}{2(a-b)(a+b)}*\frac{2a}{a+b}-\frac{b}{a-b} =  \\ \frac{(a+b)^{2}}{2(a-b)(a+b)}*\frac{2a}{a+b}-\frac{b}{a-b} =  \\ \frac{a}{a-b}-\frac{b}{a-b} =  \\ \frac{a-b}{a-b} = 1

Похожие вопросы
Предмет: География, автор: Zlobniy21